Mobilization upon Cooling. Issue 35 (16th July 2021) - Aeschlimann, Simon; Lyu, Lu; Becker, Sebastian; Mousavion, Sina; Speck, Thomas; Elmers, Hans‐Joachim; Stadtmüller, Benjamin; Aeschlimann, Martin; Bechstein, Ralf; Kühnle, Angelika
Abstract: Phase transitions between different aggregate states are omnipresent in nature and technology. Conventionally, a crystalline phase melts upon heating as we use ice to cool a drink. Already in 1903, Gustav Tammann speculated about the opposite process, namely melting upon cooling. So far, evidence for such "inverse" transitions in real materials is rare and limited to few systems or extreme conditions. Here, we demonstrate an inverse phase transition for molecules adsorbed on a surface. Molybdenum tetraacetate on copper(111) forms an ordered structure at room temperature, which dissolves upon cooling. This transition is mediated by molecules becoming mobile, i.e., by mobilization upon cooling. This unexpected phenomenon is ascribed to the larger number of internal degrees of freedom in the ordered phase compared to the mobile phase at low temperatures. Abstract : We all know that ice becomes liquid upon heating. In contrast, melting upon cooling is an unusual behavior. A system of molecules adsorbed to a surface, which become mobile upon cooling, was developed. The key for understanding these counterintuitive phase transitions lies in the fact that the high temperature ordered phase possesses more degrees of freedom leading to a larger entropy than the low‐temperature unordered phase.